2015
DOI: 10.1093/infdis/jiv063
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological Prevalence of Multiple Species of Filoviruses in Fruit Bats (Eidolon helvum) Migrating in Africa

Abstract: Fruit bats are suspected to be a natural reservoir of filoviruses, including Ebola and Marburg viruses. Using an enzyme-linked immunosorbent assay based on the viral glycoprotein antigens, we detected filovirus-specific immunoglobulin G antibodies in 71 of 748 serum samples collected from migratory fruit bats (Eidolon helvum) in Zambia during 2006-2013. Although antibodies to African filoviruses (eg, Zaire ebolavirus) were most prevalent, some serum samples showed distinct specificity for Reston ebolavirus, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 22 publications
2
117
0
1
Order By: Relevance
“…Moreover, EBOV antibodies have also been detected in other nonhuman primate species and additional insectivorous and frugivorous bat species in areas where no Ebola outbreaks have been documented yet (6). Many uncertainties still remain regarding the ecology of Ebola viruses, how they are maintained between outbreaks in wildlife, and the role of wildlife, because EBOV can also cause disease in certain species, especially chimpanzees and gorillas (7,8).…”
mentioning
confidence: 99%
“…Moreover, EBOV antibodies have also been detected in other nonhuman primate species and additional insectivorous and frugivorous bat species in areas where no Ebola outbreaks have been documented yet (6). Many uncertainties still remain regarding the ecology of Ebola viruses, how they are maintained between outbreaks in wildlife, and the role of wildlife, because EBOV can also cause disease in certain species, especially chimpanzees and gorillas (7,8).…”
mentioning
confidence: 99%
“…Although BDBV is related to EBOV, phylogenetic analysis indicates that these two viruses are antigenically distinct, with only 60% sequence similarity for the glycoprotein at the amino acid level (2,3). The natural reservoir for these viruses remains unknown; however, serological evidence suggests that fruit bats may serve as an animal host for EBOV (4,5).…”
mentioning
confidence: 99%
“…Amman et al (2012) investigated the Python Cave inhabited by the Egyptian Fruit Bat in Uganda and detected viral nucleic sequences of MARV; also seven of the bats yielded Marburg virus isolates (Table 1). Using an enzyme-linked immunosorbent assay based on the viral glycoprotein antigens, Ogawa et al (2015) detected IgG ZEBOV, and MARV in serum samples collected from the fruit bats (Eidolon helvum) in Zambia during 2006-2013. Distinct specificity for Reston ebolavirus, so far known only from Philippines and China, in Asia (Barrette et al, 2009;Pan et al, 2014), has been shown also from E. helvum for the first time in Zambia (Ogawa et al, 2015).…”
Section: Chiropteran As Probable Natural Reservoirs Of Filovirusesmentioning
confidence: 99%
“…Using an enzyme-linked immunosorbent assay based on the viral glycoprotein antigens, Ogawa et al (2015) detected IgG ZEBOV, and MARV in serum samples collected from the fruit bats (Eidolon helvum) in Zambia during 2006-2013. Distinct specificity for Reston ebolavirus, so far known only from Philippines and China, in Asia (Barrette et al, 2009;Pan et al, 2014), has been shown also from E. helvum for the first time in Zambia (Ogawa et al, 2015). Serological evidence of antibodies directed against flaviviruses and detection of viral nucleic acid incriminate those chiropters as potential reservoirs of filoviruses in nature.…”
Section: Chiropteran As Probable Natural Reservoirs Of Filovirusesmentioning
confidence: 99%
See 1 more Smart Citation